Imaging response assessment following stereotactic body radiotherapy for solid tumour metastases of the spine: Current challenges and future directions. Issue 3 (15th April 2020) - O'Sullivan, Siobhra; McDermott, Ronan; Keys, Maeve; O'Sullivan, Maeve; Armstrong, John; Faul, Clare
Abstract: Patients with metastatic disease are routinely serially imaged to assess disease burden and response to systemic and local therapies, which places ever‐expanding demands on our healthcare resources. Image interpretation following stereotactic body radiotherapy (SBRT) for spine metastases can be challenging; however, appropriate and accurate assessment is critical to ensure patients are managed correctly and resources are optimised. Here, we take a critical review of the merits and pitfalls of various imaging modalities, current response assessment guidelines, and explore novel imaging approaches and the potential for radiomics to add value in imaging assessment.